2017
DOI: 10.1111/imm.12860
|View full text |Cite
|
Sign up to set email alerts
|

Larval Echinococcus multilocularis infection reduces dextran sulphate sodium‐induced colitis in mice by attenuating T helper type 1/type 17‐mediated immune reactions

Abstract: SummaryThe tumour‐like growth of larval Echinococcus multilocularis tissue (causing alveolar echinococcosis, AE) is directly linked to the nature/orientation of the periparasitic host immune‐mediated processes. Parasite‐mediated immune suppression is a hallmark triggering infection outcome in both chronic human and murine AE. So far, little is known about secondary systemic immune effects of this pathogen on other concomitant diseases, e.g. endogenous gut inflammation. We examined the influence of E. multilocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The pathogenesis of CD and UC is usually considered to be different, with CD is dominated by IFN-γ and IL-17A from Th1 and Th17 cells, respectively, and UC mediated by IL-4 and IL-13 from Th2 cells [ 1 ]. Consistent with the findings in mice with DSS-induced acute colitis [ 31 33 ], the expression of IL-17 mRNA in the splenocytes and of IFN-γ and IL-17 mRNA in the colon increased in the DSS and/or DSS/PBS groups. However, SJMHE1 treatment reduced the expression levels of IFN-γ and IL-17 mRNA, increased the expression levels of IL-4, TGF-β and IL-35 mRNA in the splenocytes and increased the expression levels of IL-4, IL-10, TGF-β and IL-35 mRNA in the colon of mice.…”
Section: Discussionsupporting
confidence: 87%
“…The pathogenesis of CD and UC is usually considered to be different, with CD is dominated by IFN-γ and IL-17A from Th1 and Th17 cells, respectively, and UC mediated by IL-4 and IL-13 from Th2 cells [ 1 ]. Consistent with the findings in mice with DSS-induced acute colitis [ 31 33 ], the expression of IL-17 mRNA in the splenocytes and of IFN-γ and IL-17 mRNA in the colon increased in the DSS and/or DSS/PBS groups. However, SJMHE1 treatment reduced the expression levels of IFN-γ and IL-17 mRNA, increased the expression levels of IL-4, TGF-β and IL-35 mRNA in the splenocytes and increased the expression levels of IL-4, IL-10, TGF-β and IL-35 mRNA in the colon of mice.…”
Section: Discussionsupporting
confidence: 87%
“…The regulation of parasite-specific immune response affects not only helminth antigens, but also unrelated antigens. In recent years, clinical and experimental evidence has demonstrated that infection with parasitic helminth protects hosts from IBD; for example, a case control study in South Africa demonstrated protective association of childhood helminth infection against the development of IBD ( 10 ) ; pre-existing helminth Echinococcus multilocularis ( 11 ), Heligmosomoides polygyrus ( 12 ), or Hymenolepis diminuta ( 13 ), etc., infection have been shown to reduce chemically-induced colitis in mice by modulating the immune responses of their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…CD is dominated by IFN-γ and IL-17A from Th1 and Th17 cells, respectively, whereas UC is mediated by IL-4 and IL-13 from Th2 cells [1]. Consistent with the ndings in mice with DSS-induced acute colitis [29,30,31], the mRNA expression of IL-17 in the splenocytes and the mRNA expression of IFN-γ and IL-17 in the colon increased in the DSS and DSS/PBS groups. However, SJMHE1 treatment reduced the mRNA expression levels of IFN-γ and IL-17, increased the mRNA expression levels of IL-4 and TGF-β in the splenocytes, and increased the mRNA expression levels of IL-4, IL-10, TGF-β, and IL-35 in the colon of mice.…”
Section: Discussionmentioning
confidence: 56%